Huangkui Capsule Ameliorates Renal Fibrosis in a Unilateral Ureteral Obstruction Mouse Model Through TRPC6 Dependent Signaling Pathways - Gu, Li-fei; Ge, Hai-tao; Zhao, Lei; Wang, Yu-jing; Zhang, Fan; Tang, Hai-tao; Cao, Zheng-yu; Yu, Bo-yang; Chai, Cheng-zhi (Frontiers in Pharmacology, 2020)
Renal fibrosis is the final common pathological manifestation of almost all progressive chronic kidney diseases (CKD). Transient receptor potential canonical (TRPC) channels, especially TRPC3/6, were proposed to be essential therapeutic targets for kidney injury. Huangkui capsule (HKC), an important adjuvant therapy for CKD, showed superior efficacy for CKD at stages 1-2 in clinical practice. However, its anti-fibrotic effect and the underlying mechanisms remain to be investigated. In the present study, we evaluated the efficacy of HKC on renal fibrosis in a mouse model of unilateral ureteral obstruction (UUO) and explored the potential underlying mechanism. Administration of HKC by intragastric gavage dose-dependently suppressed UUO-induced kidney injury and tubulointerstitial fibrosis. Similarly, HKC suppressed the expression level of α-smooth muscle actin (α-SMA), increased the expression of E-cadherin, and suppressed the mRNA expression of a plethora of proinflammatory mediators that are necessary for the progression of renal fibrosis. Mechanistically, HKC suppressed both canonical and non-canonical TGF-β signaling pathways in UUO mice as well as the TRPC6/calcineurin A (CnA)/nuclear factor of activated T cells (NFAT) signaling axis. In addition, TRPC6 knockout mice and HKC treated wild type mice displayed comparable protection on UUO-triggered kidney tubulointerstitial injury, interstitial fibrosis, and α-SMA expression. More importantly, HKC had no additional protective effect on UUO-triggered kidney tubulointerstitial injury and interstitial fibrosis in TRPC6 knockout mouse. Further investigation demonstrated that HKC could directly suppress TRPC3/6 channel activities. Considered together, these data demonstrated that the protective effect of HKC on renal injury and interstitial fibrosis is dependent on TRPC6, possibly through direct inhibition of TRPC6 channel activity and indirect suppression of TRPC6 expression.